Retroperitoneal lymphocele. Complication abdominal aortic surgery - Cazabán, Luis; Pose, Juan; López, Daniel; Puñal, Alicia (Cirugía del Uruguay, 2001)
A retroperitoneal lymphocele subsequent to abdominal aortic surgery is a rare and severe condition. Lymph extravasation determines severe denutrition and increase of operative mortality.